Questioning the benefit of restrictive transfusion practice in older adults. (7th September 2018) - Simon, Geoff I.; Craswell, Alison; Thom, Ogilvie; Fung, Yoke Lin
Abstract : Restrictive transfusion practice is widely promoted, with many international guidelines recommending haemoglobin thresholds of 70 to 80 g/l for adult patients who are asymptomatic. Randomized controlled trials comparing outcomes associated with liberal and restrictive transfusion strategies underpin this approach. Meta‐analyses including trials of adult patients >18 years of age have concluded that restrictive practice is noninferior to liberal transfusion approaches. A restrictive approach to transfusion reduces resource consumption and cost, as well as the hazards associated with unnecessary exposure to blood products. Although adults aged ≥65 years consume over half of the blood supply, there are few randomized controlled transfusion trials exclusive to this cohort. Our 2017 meta‐analysis of a small number of trials focussed on older adults found that higher transfusion haemoglobin thresholds were associated with lower mortality and fewer cardiac complications in this age group. Other studies have also shown that higher transfusion haemoglobin thresholds are beneficial in older adults. This paper presents recent evidence regarding transfusion outcomes in older adults and discusses aspects of the pathophysiology of ageing that impact on the reduced resilience of older patients to anaemic states. This evidence challenges the use of Hb thresholds that apply across the adult lifespan, regardless of age. It proposes that older age be considered as a risk factor in assessing transfusion requirements, and that transfusion practice in older adults may require higher haemoglobin thresholds than for younger adults.